Geochemical transect through a travertine mount: A detailed record of CO2-enriched fluid leakage from Late Pleistocene to present-day – Little Grand Wash fault (Utah, USA). (12th May 2017) - Frery, Emanuelle; Gratier, Jean-Pierre; Ellouz-Zimmerman, Nadine; Deschamps, Pierre; Blamart, Dominique; Hamelin, Bruno; Swennen, Rudy
Abstract: Active and fossil endogenic travertine mounts scattered along the Little Grand Wash fault are studied as records of Quaternary CO2 -enriched fluid leakage. This study focusses on a particular area where a fossil mount formed in a near-surface setting by successive circulation/sealing episodes from Late Pleistocene to Mid-Holocene and where a modern surface travertine is still being formed by a CO2 -enriched fluid source. The fossil mount is composed of horizontal and vertical veins whereby the vertical veins recorded numerous cycles of circulation/sealing/dissolution events and were used as conduits for the CO2 -enriched fluid circulation from the depth to the surface or along sub-horizontal fractures where successive precipitation events are recorded. The modern travertine is being built at the surface by successive eruption of Crystal Geyser, an anthropic geyser active since the 1930's. δ 13 C and δ 18 O signatures and U/Th datings, ranging from 11.5 ky till present-day allows calibrating in detail the CO2 enriched fluid leakage along a single fault segment and in a post glacial context, as last glaciations in the study area took place 15 ky ago. The dataset shows a high decrease of the oxygen stable isotope values till about 6 ky, then the variations reflect a constant range until present-day. This tends to restrain the period of local increase of the meteoric water input in the aquifer that is sourcing the CO2 -enriched water. The fossil travertine represents a 7 ky-long record of CO2 leakage above a natural reservoir, from Late Pleistocene to Mid-Holocene. The flux of CO2 leakage through time and the total escaping volume have been computed and appears to be low in comparison with an anthropogenic leak provoked, for instance, by a non-sealed well.